Method of immobilizing compound on solid phase support (2003)
The present invention provides a method of analyzing the specific interaction between a molecule to be analyzed and a molecule that specifically interacts with the former molecule on a solid phase using a molecule-immobilized solid phase support mixture prepared by binding the subject molecule to the solid phase support without specifying the binding position on the molecule side, particularly a method wherein the immobilization is conducted via a spacer introduced to the molecule without specifying the binding position on the molecule side, which method makes it possible to identify and select only a molecule that exhibits a specific interaction with a molecule to be analyzed, without an investigation of structure-activity correlation, which has conventionally been essential, and hence enables an analysis of the interaction between these molecules.